Islamic bank retail financing products and services: A critical assessment - Saiti, Buerhan; Abdul Wahab, Hishamuddin; Ahmad, Khaliq (Beşiz Publications, 2016)
This paper discusses the Islamic bank retail financing, its instruments and operations. The discussion demonstrates that it is essential to have a banking system based on Shariah principles which fulfill needs of Muslim consumers. The paper examines the various personal financing products, their underlying Islamic contracts and their computation mechanisms with appropriate examples. It also evaluates critically products of Islamic bank retail financing. The availability of various personal financing instruments in Islamic banks allows Muslim consumers to achieve their financing needs. Moving forward, more variety of instruments which invite less Shariah issues must be offered in the market to ensure a more vibrant Islamic banking system